2015
DOI: 10.1088/0957-4484/26/15/155704
|View full text |Cite
|
Sign up to set email alerts
|

CdTe and graphene co-sensitized TiO2nanotube array photoanodes for protection of 304SS under visible light

Abstract: CdTe/graphene/TiO2 films that served as photoanodes for cathodic protection application were prepared by an electrochemical deposition method. The deposition of graphene and CdTe nanoparticles (NPs) on the surface of the TiO2 nanotubes was confirmed by scanning electron microscope and transmission electron microscopy. The composites exhibited high light absorption in both the UV and visible light region. The results indicated that TiO2 nanotube photoelectrodes sensitized by 20-cycle graphene and 30-cycle CdTe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The potential change to more negative values during illumination is characteristic for n-type semiconductors. 34 Since the number of photogenerated charges is equivalent, these results prove that the reason for a better performance of the TNT-AuNW is rather faster electron transfer through the metal NWs and better charge separation due to the Schottky barrier, while TNT-Ti suffers from high electron-hole recombination. Note that the results presented in Fig.…”
Section: Photoelectrochemical Water Splitting On Tnt-aunw Electrodesmentioning
confidence: 71%
“…The potential change to more negative values during illumination is characteristic for n-type semiconductors. 34 Since the number of photogenerated charges is equivalent, these results prove that the reason for a better performance of the TNT-AuNW is rather faster electron transfer through the metal NWs and better charge separation due to the Schottky barrier, while TNT-Ti suffers from high electron-hole recombination. Note that the results presented in Fig.…”
Section: Photoelectrochemical Water Splitting On Tnt-aunw Electrodesmentioning
confidence: 71%
“…Their results show that under visible light irradiation, the ternary composite material has a stronger light response than pure TiO 2 , and its photoelectrochemical performance is significantly enhanced. Li [ 34 ] et al fabricated CdTe/graphene/TiO 2 films by an electrochemical deposition method, where their results show that CdTe/graphene/TiO 2 composite materials exhibit high light absorption in both ultraviolet and visible light regions, and offer a good photocathode protection performance. Although many studies can be found in the literature concerning the use of ternary TiO 2 hybrids as photoanodes for PCP, it generally requires two corrosion cells and photoanode cells connected by wires.…”
Section: Introductionmentioning
confidence: 99%
“…The charges stored in the Bi 2 S 3 /TiO 2 composite were released and again transferred to 304SS in the dark. The negative shift of potentials is reportedly an important parameter for evaluating the separation efficiency of photogenerated charges [39, 40]. The increased negative shift of the potentials indicates the increased effectiveness of the cathodic protection of photoanodes.…”
Section: Resultsmentioning
confidence: 99%